Augmenting trauma-focused psychotherapy for post-traumatic stress disorder with brief aerobic exercise in Australia: a randomised clinical trial. (January 2023) - Bryant, Richard A; Dawson, Katie S; Azevedo, Suzanna; Yadav, Srishti; Cahill, Catherine; Kenny, Lucy; Maccallum, Fiona; Tran, Jenny; Rawson, Natasha; Tockar, Julia; Garber, Benjamin; Keyan, Dharani
Summary: Background: Although exposure therapy is central in most front-line psychotherapies of post-traumatic stress disorder (PTSD), many patients do not respond to this treatment. We aimed to investigate the effects of brief aerobic exercise on the efficacy of exposure therapy in reducing the severity of PTSD. Methods: We did a single-blind, parallel, randomised controlled trial in Sydney, NSW, Australia. We included adults (aged ≥18 years) with clinician-diagnosed PTSD. We excluded participants aged 70 years or older, with imminent suicidal risk (reporting suicidal plan), presence of psychosis or substance dependence, history of moderate-to-severe traumatic brain injury, or presence of a physical disorder or impairment that might be exacerbated by aerobic exercise (eg, back pain). We randomly assigned participants (1:1) to nine 90-min weekly sessions of exposure therapy for PTSD with 10 min aerobic exercise or to the control group of exposure therapy with 10 min passive stretching. The primary outcome was PTSD severity measured by the clinician-administered PTSD scale 2 (CAPS-2), independently assessed at baseline, 1 week after treatment, and 6 months after treatment (primary outcome timepoint). Findings: Between Dec 12, 2012, and July 25, 2018, we enrolled 130 participants with PTSD, with 65 (50%) participants randomly assigned to exposure therapy with exercise and 65 (50%) to exposure therapy with passive stretching, including 79 (61%) women and 51 (39%) men, with a mean age of 39·1 years (SD 14·4; range 18–69). 99 (76%) participants were White, 14 (11%) were Asian, and 17 (13%) were listed as other. At the 6-month follow-up assessment, participants in the exposure therapy with exercise group showed greater reductions in CAPS-2 scores relative to those in the exposure therapy with stretching group (mean difference 12·1 [95% CI 2·4–21·8]; p=0·023), which resulted in a moderate effect size of 0·6 (0·1–1·1). No adverse events associated with the intervention were reported. The trial was prospectively registered on the Australian and New Zealand Clinical Trials Registry, ACTRN12612000185864. Interpretation: Brief aerobic exercise has the potential to augment long-term gains of exposure therapy for PTSD, which accords with evidence from studies in animals and humans on the role of exercise in modulating the extinction learning processes. This strategy might offer a simple and affordable means to augment treatment gains for exposure therapy in people with PTSD. Funding: Australian National Health and Medical Research Council.